Partisanship and Survey Refusal - Mark Borgschulte; Heepyung Cho; Darren Lubotsky (Institute of Labor Economics (IZA), 2022)
Response rates to important surveys used in social science research have been falling precipitously over the last few decades, raising questions about the representativeness of the resulting data and the quality of evidence that comes from it. We examine how partisan preferences influence response to the Current Population Survey (CPS). Using U.S. state and metro vote shares or an individual-level model based on the longitudinal structure of the CPS, we find evidence of a political cycle in refusals, but that partisanship does not explain the surge in refusals since 2009. Evidence from a natural experiment in Tea Party support using rain on the day of the first Tea Party rally indicates the anti-Census and anti-survey rhetoric of the Tea Party did not increase refusals.
Keywords: C81; J64; P48; 330; Current Population Survey; survey refusal; unit non-response; unemployment rate